Extensor hallucis longus tendon rupture and reconstruction using allograft tendon: a case report and literature review - Sidhu, Gur Aziz Singh; Bodgener, Isabel; Bhamra, Jagmeet Singh (International Journal of Research in Orthopaedics, 2025)
This case report examined tendon reconstruction using allograft as a treatment approach for chronic extensor hallucis longus (EHL) tendon ruptures, an area with limited existing research. Two cases were discussed to evaluate this method’s effectiveness. The first case involved a 27-years-old male (Patient A) with an EHL tendon tear with retraction up to 2.2 cm and an additional 1.6 cm gap in the extensor hallucis brevis (EHB) tendon confirmed on imaging. The second case was a 28-years-old female (Patient B) with a spontaneous rupture of the left EHL tendon tear with retraction to the tarsometatarsal joint and proximal attenuation extending to the ankle joint. Both patients received reconstruction with an allograft, performed using Kessler’s technique, reinforced with epitenon sutures. Postoperatively, they remained non-weight bearing for four weeks with early range of motion. At the 3-months follow-up, both patients demonstrated active hallux extension and full range of motion, reporting no discomfort during daily activities. Improvements were noted on the American Orthopedic Foot and Ankle Society (AOFAS) Hallux Metatarsophalangeal-Interphalangeal scale and Foot and Ankle ability Measure (FAAM) scores, including the Activities of Daily Living and Sports subscales.